Validation of the cosmed k4b2 portable metabolic system during running outdoors - Ross, R.; Al Duhishy, A.; González-Haro, C. (The Journal of Strength and Conditioning Research, 2020)
The aim of this study was to determine the agreement of the K4b2 metabolic system in comparison with the Douglas bags (DB) method for determining gas-exchange variables during both indoor treadmill and outdoor running. Nineteen endurance-trained males undertook 3 maximal incremental running tests, separated by at least 2 days: K4b2 indoor test (K1), K4b2 outdoor test (K2), and DB indoor test. Gas-exchange parameters (VO2, VCO2, VE, VI, Respiratory Exchange Ratio, FEO2, and FECO2) and heart rate were measured during K1, K2, and DB tests. For most of the variables (VO2, %VO2, %VCO2, VE, and VI), the agreement was better for K2 when compared with DB than for K1 when compared with DB. For VCO2, FEO2, and FECO2, the agreement was better between K1 when compared with DB than for K2 when compared with DB. Respiratory Exchange Ratio showed a similar agreement between both conditions (K1 vs. DB and K2 vs. DB). K4b2 seems valid for measuring gas-exchange variables during submaximal and maximal running velocities in an outdoor environment. Although K2 mean systematic error (bias) was low, the aleatory error was moderate. These considerations should be taken into account when using K4b2 to measure gas-exchange parameters both during indoor and outdoor activities.